Effect of HIV-1 envelope cytoplasmic tail on adenovirus primed virus encoded virus-like particle immunizations. Issue 44 (17th October 2016) - Andersson, Anne-Marie C.; Ragonnaud, Emeline; Seaton, Kelly E.; Sawant, Sheetal; Folgori, Antonella; Colloca, Stefano; Labranche, Celia; Montefiori, David C.; Tomaras, Georgia D.; Holst, Peter J.
Highlights: Adenoviral heterologous prime-double boost continuously increase antibody responses. CON-S CT truncation increases antigen presentation with a bias towards gp120 epitopes. Priming with an Env CT truncated VLP vaccine skews antibody responses towards gp120. Abstract: The low number of envelope (Env) spikes presented on native HIV-1 particles is a major impediment for HIV-1 prophylactic vaccine development. We designed virus-like particle encoding adenoviral vectors utilizing SIVmac239 Gag as an anchor for full length and truncated HIV-1 M consensus Env. Truncated Env overexpressed VRC01 and 17b binding antigen on the surface of transduced cells while the full length Env vaccine presented more and similar amounts of antigen binding to the trimer conformation sensitive antibodies PGT151 and PGT145, respectively. The adenoviral vectors were used to prime Balb/c mice followed by sequential boosting with chimpanzee type 63, and chimpanzee type 3 adenoviral vectors encoding SIVmac239 Gag and full length consensus Env. Both vaccine regimens induced increasing titers of binding antibody responses after each immunization, and significant differences in immune responses between the two groups were observed after the final immunization. Full length Env priming skewed antibody responses towards gp41, while truncated Env priming induced responses primarily targeting gp120 containing and derived antigens. Importantly, no differences in neutralizing antibody responses were found between the different priming regimens as both induced high titered tier 1 neutralizing antibodies, but no tier 2 antibodies, possibly reflecting the similar presentation of trimer specific antibody epitopes. The described vaccine regimens provide insight into the effects of the HIV-1 Env cytoplasmic tail on epitope presentation and subsequent immune responses, which is relevant for the interpretation of current clinical trials that are using truncated Env as an immunogen. The regimens described here provide similar neutralization titers, and thus are useful for investigating the importance of specificity in non-neutralizing antibody mediated protection against viral challenge.